CRYPTOSPORIDIUM PARVUM AS RISK FACTOR ON NEONATAL DIARRHEA IN ALPACAS OF PUNO - Molina M., Daniel (2009)
The role of Cryptosporidium parvum as a risk factor for the occurrence of neonatal diarrhea was evaluated using a case-control study design in alpacas from Puno. The study was carried out during the calving season, between February and March 2006. Stool samples (n=487) were collected in alpacas of 1 to 15 days of age in four localities: Antacalla, La Raya, Quimsachata and Macusani. The faecal smears were processed following the Modified Ziehl-Neelsen stain. The 39% (130/336) of alpacas with diarrhea and 23% (35/151) of alpacas without diarrhea were positives to C. parvum infection. The logistic regression showed that this parasite does not represent a risk factor for neonatal diarrhea in the screened animals (OR: 1.5, IC 95%: 0.9-2.4). It was also determined that La Raya was statistically significant (p=0.046) and represented a risk factor for the occurrence of neonatal diarrhea (OR: 2.5, IC 95%: 1.1-6.1).